Diversity of Sapodilla (Achras zapota L.) Growth from Wonogiri and Bojonegoro in Different Age of Transplantation Seed - Endang Yuniastuti; Muhammad Agung; Parjanto Parjanto (Pusat Penelitian dan Pengembangan Bioteknologi dan Biodiversitas (P3BB) LPPM UNS, 2022)
Most farmers determine the cutting of air layer seed in a corp through the amount of the growing roots from air layer itself. The roots can be an indicator of air layer cutting method in a corp. The roots, which are too old or too young, grow less optimal in the air layer seed after being transferred into another cultivated medium. It is necessary to have knowledge about the precise age of air layer cutting so that the vegetative propagation by using air layer can be performed accurately and efficiently. The treatment that is executed is the age of air layer and the corps accession. The result of this research indicates that the effect of the difference air layer age on plant growth is at the age of emerging buds, aged 180 Day is treated with the age of the fastest emerging shoots. The growth of Bojonegoro air layer plants results that does not differ with Wonogiri air layer plants. There is no interaction between air layer age with sapodilla accession on plant growth.